PENGARUH PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA TRIMINO TERHADAP KECEPATAN SISWA KELAS V DALAM MENYELESAIKAN SOAL MATEMATIKA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determie the effect of cooperative learning assisted by trimino media on speed in solving math problems. This research uses quantitative metods. This type of research is a quasi-experimental design with nonequivalent control group design. The sampling technique was purposive sampling. The number of stdents who carried out this research was 60 students, of which 30 students in the experimental class and 30 students in the control class. The data collection techniques used were pre-test and post-test. The data analysis technique used the t-test which had previously been tested for homogeneity and normality. The results of the t-test hypothesis test showed tcount (3,695) > ttable (2,001) with a significance level of 5%. This means that there is a positive influence between cooperative learning assisted by trimino media on the speed of grade V student in solving math problems.Key Words: Cooperative Learning; Trimino Media Matemathic, Speed